Negative electrode slurry, negative electrode plate and battery

By adding conductive agent with a porous structure and a highly swellable polymer to the negative electrode slurry of the lithium-ion battery, the problem of insufficient kinetic performance of the lithium-ion intercalation is solved, and the fast charging and cycling performance of the battery is significantly improved.

CN119890221APending Publication Date: 2025-04-25ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2

Patent Information

Application Number
CN202510011230.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The fast charging performance of lithium-ion batteries is limited by the insufficient kinetic performance of lithium-ion intercalation in the negative electrode graphite material, resulting in a decrease in battery capacity, precipitation of lithium metal and safety risks.

Method used

A negative electrode slurry is proposed, including an anode active material, a conductive agent with a porous structure and a highly swellable polymer. By improving the lithium ion transmission performance, the ability to absorb and retain the electrolyte, the interface transfer resistance is reduced, thereby improving the fast charging performance and cycling performance of the battery.

Benefits of technology

By increasing the lithium ion transmission channel and improving the infiltration capacity of the electrolyte, the fast charging and cycling performance of the battery is significantly improved, and the risk of lithium metal precipitation is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides negative electrode slurry, a negative electrode plate and a lithium ion battery. The negative electrode slurry comprises a negative electrode active material, a conductive agent with a porous structure and a high-swelling polymer. Therefore, the conductive agent with the porous structure can provide more lithium ion transmission channels, and the ionic conductivity can be improved; and the high-swelling-rate polymer can improve the infiltration capacity of the electrolyte on the surface of the negative plate, reduce the interface transfer resistance and improve the electrolyte absorption and retention capacity of the negative plate. Therefore, the fast charging performance and the cycle performance of the battery can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and specifically, to negative electrode slurry, negative electrode sheet and lithium ion battery. Background Art

[0002] With the popularity of electric vehicles, the market has put forward higher requirements for the fast charging capability of lithium-ion batteries. In order to alleviate the range anxiety caused by long charging time and promote the growth of electric vehicle market share, improving the fast charging performance of batteries has become particularly important. However, one of the main limiting factors of fast charging performance is the lithium ion (Li) in the negative electrode graphite material. + ) have insufficient intercalation kinetics. The slow intercalation of lithium ions into graphite can lead to decreased battery capacity, lithium metal precipitation, and potential safety risks. To overcome these challenges, the key is to optimize the formulation and structural design of the negative electrode sheet to ensure that lithium ions can be quickly and effectively intercalated into the negative electrode graphite material and diffuse rapidly therein, thereby significantly improving the battery's charge and discharge rate performance. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to provide a negative electrode slurry, a negative electrode sheet and a battery. The negative electrode slurry of the present application can provide more lithium ion channels, while improving the electrolyte's ability to wet the surface of the negative electrode material, reducing the interface transfer resistance, thereby improving the fast charging performance and cycle performance of the battery.

[0004] In the first aspect of the present application, the present application proposes a negative electrode slurry. According to an embodiment of the present application, the negative electrode slurry includes: a negative electrode active material, a conductive agent with a porous structure, and a highly swellable polymer. As a result, the negative electrode slurry of the present application can improve the lithium ion transmission performance, the ability to absorb electrolyte (liquid absorption) and retain electrolyte (liquid retention). Among them, the conductive agent with a porous structure can, on the one hand, increase more lithium ion transmission channels and increase the diffusion rate of lithium ions in the negative electrode material, thereby improving the rate performance of the battery, that is, the ability of the battery to charge and discharge at high current density; on the other hand, it can increase the porosity of the negative electrode sheet, and the high porosity helps the electrolyte to better penetrate and fill into the microstructure of the negative electrode material, thereby improving the liquid absorption and liquid retention capacity of the negative electrode sheet. On the one hand, the high swelling polymer can improve the electrolyte's ability to wet the surface of the negative electrode material, reduce the interface transfer resistance, and thus improve the battery's charge and discharge efficiency; on the other hand, it can improve the affinity between the negative electrode sheet and the electrolyte, so that the negative electrode sheet can more effectively absorb and retain the electrolyte, thereby improving the battery's electrochemical performance. Therefore, by adding a conductive agent with a porous structure and a high swelling polymer to the negative electrode slurry at the same time, the battery's fast charging performance and cycle performance can be improved.

[0005] According to an embodiment of the present application, the negative electrode slurry may further include at least one of the following additional technical features:

[0006] According to an embodiment of the present application, based on the total mass of the negative electrode slurry, the mass proportion of the conductive agent having a porous structure is 0.5%-5%.

[0007] According to an embodiment of the present application, based on the total mass of the negative electrode slurry, the mass proportion of the highly swellable polymer is 0.1%-1%.

[0008] According to an embodiment of the present application, the conductive agent includes at least one of carbon black, graphite, and activated carbon.

[0009] According to an embodiment of the present application, the negative electrode active material includes at least one of a carbon material or an alloy material.

[0010] According to an embodiment of the present application, the pore size of the porous structure is no greater than 50 nm.

[0011] According to an embodiment of the present application, the specific surface area of ​​the conductive agent is 200 m 2 / g-2000m 2 / g.

[0012] According to an embodiment of the present application, the carbon material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, petroleum coke, carbon fiber, pyrolytic carbon, and resin carbon.

[0013] According to an embodiment of the present application, the alloy material includes at least one of a tin-based alloy, a silicon-based alloy, a germanium-based alloy, an aluminum-based alloy, an antimony-based alloy, and a magnesium-based alloy.

[0014] According to an embodiment of the present application, the highly swellable polymer includes at least one of polyacrylate, polyacrylamide, and modified polyethylene oxide.

[0015] According to an embodiment of the present application, the modified polyethylene oxide includes at least one of maleic anhydride-modified polyethylene oxide, acrylic anhydride-modified polyethylene oxide, methacrylic anhydride-modified polyethylene oxide, fumaric acid-modified polyethylene oxide, acrylic acid-modified polyethylene oxide, and methacrylic acid-modified polyethylene oxide.

[0016] According to an embodiment of the present application, the modified polyethylene oxide is obtained by the following method: a modified monomer is subjected to an esterification reaction with polyethylene oxide to obtain the modified polyethylene oxide; wherein the modified monomer includes at least one of maleic anhydride monomer, acrylic anhydride monomer, methacrylic anhydride monomer, fumaric acid monomer, acrylic acid monomer, and methacrylic acid monomer.

[0017] According to an embodiment of the present application, the weight ratio of the modified monomer to the polyethylene oxide is (0.2:30)-(1:70).

[0018] According to an embodiment of the present application, the solvent for the esterification reaction is tetrahydrofuran (THF).

[0019] According to an embodiment of the present application, the esterification reaction is carried out under the action of a catalyst 4-dimethylaminopyridine (DMAP).

[0020] According to an embodiment of the present application, the esterification reaction is carried out at 60° C. to 80° C. for 4 h to 8 h.

[0021] According to an embodiment of the present application, at least one of a thickener and a binder is further included.

[0022] According to an embodiment of the present application, the thickener includes at least one of sodium carboxymethyl cellulose (CMC-Na) and lithium carboxymethyl cellulose (CMC-Li).

[0023] According to an embodiment of the present application, the binder includes at least one of styrene butadiene rubber (SBR) and polyacrylate (PAA).

[0024] According to an embodiment of the present application, the mass ratio of the negative electrode active material, the conductive agent having a porous structure, the highly swellable polymer, the thickener and the binder is (90-98):(0.5-5.0):(0.1-1.0):(0.5-3):(0.8-5.0).

[0025] In the second aspect of the present application, the present application proposes a negative electrode sheet. According to an embodiment of the present application, the negative electrode sheet is prepared from the negative electrode slurry described in the first aspect. As mentioned above, the negative electrode slurry of the present application can provide more lithium ion channels, improve ion conductivity, and have good electrolyte absorption and electrolyte retention capabilities. Therefore, the electrode sheet prepared using the negative electrode slurry of the present application has good conductivity and can improve the cycle performance and high rate performance of lithium-ion batteries. Those skilled in the art can understand that the negative electrode sheet has all the characteristics and advantages of the negative electrode slurry described above, and will not be repeated here.

[0026] In the third aspect of the present application, the present application proposes a battery. According to an embodiment of the present application, the battery includes the negative electrode sheet described in the second aspect. As a result, the lithium-ion battery of the present invention has better cycle performance, high rate performance, etc. It can be understood by those skilled in the art that the lithium-ion battery has all the features and advantages of the negative electrode slurry described above, and no further elaboration is given here.

[0027] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION

[0028] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.

[0029] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0030] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.

[0032] In this document, the terms "include" or "comprising" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0033] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0034] With the rapid development of the new energy industry, the production scale and demand of lithium-ion batteries are increasing. Lithium-ion batteries have successfully driven the vigorous development of the new energy vehicle industry and the digital consumer electronics industry due to their advantages such as high energy density, long performance life, low self-discharge rate and green environmental protection. However, the current fast charging capacity of lithium-ion batteries is limited by some key factors, namely the poor lithium ion intercalation kinetics in the negative electrode graphite, the capacity decay, lithium precipitation and safety issues caused by slow intercalation.

[0035] At present, the negative electrode of lithium-ion batteries usually adopts materials such as graphite, conductive agent, binder and thickener. For example, conductive carbon black, graphene, carbon nanotubes or composite conductive agent are used as conductive agent, styrene-butadiene rubber (SBR) or polyacrylic acid (PAA) as binder, and sodium / lithium carboxymethyl cellulose (CMC) as thickener. However, when lithium-ion batteries are charged at high currents, various polarizations lead to limited utilization of active materials, which becomes the main obstacle to fast charging performance. From the perspective of electrochemical kinetics, the main kinetic limitation comes from the overpotential caused by polarization, which is the difference between the open circuit voltage and the operating voltage. Since electronic conductivity is usually much higher than ionic conductivity, the overpotential of the negative electrode is mainly caused by lithium ions (Li + ) is caused by the diffusion and charge transfer of the negative electrode. Therefore, improving the design of the negative electrode sheet, improving the ionic conductivity and kinetic performance has become an urgent need to improve the fast charging capability and cycle performance of the battery, so as to ensure that the battery can meet the energy density requirements while adapting to the user's demand for fast charging.

[0036] Negative electrode slurry and preparation method thereof

[0037] Based on this, the present application proposes a negative electrode slurry. According to an embodiment of the present application, the negative electrode slurry includes: a negative electrode active material, a conductive agent with a porous structure and a highly swellable polymer. As a result, the negative electrode slurry of the present application can improve the lithium ion transmission performance, the ability to absorb electrolyte (liquid absorption) and retain electrolyte (liquid retention). Among them, the conductive agent with a porous structure can, on the one hand, increase more lithium ion transmission channels and increase the diffusion rate of lithium ions in the negative electrode sheet, thereby improving the rate performance of the battery, that is, the ability of the battery to charge and discharge at high current density; on the other hand, it can increase the porosity of the negative electrode sheet, and the high porosity helps the electrolyte to better penetrate and fill into the microstructure of the negative electrode material, thereby improving the liquid absorption and liquid retention capacity of the negative electrode sheet. On the one hand, the highly swellable polymer can improve the wetting ability of the electrolyte on the surface of the negative electrode material, reduce the interface transfer resistance, and thus improve the charge and discharge efficiency of the battery; on the other hand, it can improve the affinity between the negative electrode sheet and the electrolyte, so that the negative electrode sheet can more effectively absorb and retain the electrolyte, thereby improving the electrochemical performance of the battery. Therefore, by adding a conductive agent with a porous structure and a highly swellable polymer to the negative electrode slurry at the same time, the fast charging performance and cycle performance of the battery can be improved.

[0038] In some embodiments of the present application, based on the total mass of the negative electrode slurry, the mass proportion of the conductive agent with a porous structure is 0.5%-5%. For example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, etc., or can be a range composed of any of the above values. Therefore, by making the mass proportion of the conductive agent within the above range, more Li + transmission channel, improves ion conductivity, and at the same time improves the liquid absorption and liquid retention capacity of the negative electrode, thereby improving the fast charging performance and cycle performance of the battery.

[0039] In some embodiments of the present application, based on the total mass of the negative electrode slurry, the mass proportion of the high swelling polymer is 0.1%-1%. For example, it can be 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, etc., or it can be a range composed of any of the above values. Therefore, by making the mass proportion of the high swelling polymer within the above range, it is possible to improve the wetting ability of the electrolyte on the surface of the negative electrode material, reduce the interface transfer resistance, and improve the ability of the negative electrode sheet to absorb the electrolyte. At the same time, the phenomenon of increased battery impedance caused by excessive content of the high swelling polymer is avoided, thereby improving the fast charging performance and cycle performance of the battery.

[0040] In some embodiments of the present application, the conductive agent includes at least one of carbon black, graphite, and activated carbon. Therefore, the conductive agent has good conductivity, can effectively improve the conductivity of the negative electrode sheet, and has a wide range of raw material sources, low cost, and high cost performance.

[0041] In some embodiments of the present application, the pore size of the porous structure is not greater than 50 nm. For example, it can be 0.1 nm, 0.3 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, etc., or it can be a range composed of any of the above numerical values. As a result, the conductive agent can provide more lithium ion transmission channels and increase the diffusion rate of lithium ions in the negative electrode material. At the same time, increasing the porosity of the negative electrode sheet helps the electrolyte to better penetrate and fill the microstructure of the negative electrode material, improve the liquid absorption and liquid retention capacity of the negative electrode sheet, and further enhance the rate performance of the battery.

[0042] It should be noted that the porous structure in the "conductive agent with a porous structure" described in the present application can be a microporous structure or a mesoporous structure, that is, the pore size of the microporous structure is less than 2nm, for example, it can be 0.1nm, 0.3nm, 0.5nm, 1nm, 1.5nm, 1.9nm, etc., and the pore size of the mesoporous structure is 2nm-50nm, for example, it can be 2nm, 10nm, 20nm, 30nm, 40nm, 50nm, etc.

[0043] In some embodiments of the present application, the specific surface area of ​​the conductive agent is 200 m 2 / g-2000m 2 / g. For example, it can be 200m 2 / g、500m 2 / g、800m 2 / g、1000m 2 / g、1200m 2 / g、1500m 2 / g、1800m 2 / g, 2000m 2 / g, etc., or can be any range of the above values. Thus, by making the specific surface area of ​​the conductive agent within the above range, close contact between the conductive agent particles can be promoted to form a good conductive network, thereby improving the conductive performance of the negative electrode sheet; in addition, the contact area with the electrolyte can be increased, thereby improving the adsorption capacity of the electrolyte.

[0044] In some embodiments of the present application, the negative electrode active material includes at least one of a carbon material or an alloy material. Thus, the negative electrode active material can store more lithium ions and improve the energy density of the battery.

[0045] In some embodiments of the present application, the carbon material includes at least one of artificial graphite, natural graphite, mesophase carbon microspheres, petroleum coke, carbon fiber, pyrolytic carbon, and resin carbon. Thus, the carbon material selected from the above types as the negative electrode active material can enable the negative electrode active material to store more lithium ions and improve the energy density of the battery.

[0046] In some embodiments of the present application, the alloy material includes at least one of tin-based alloy, silicon-based alloy, germanium-based alloy, aluminum-based alloy, antimony-based alloy, and magnesium-based alloy. Thus, the alloy material selected from the above types as the negative electrode active material can enable the negative electrode active material to store more lithium ions and improve the energy density of the battery.

[0047] In some embodiments of the present application, the highly swellable polymer includes at least one of polyacrylate, polyacrylamide, and modified polyethylene oxide. Thus, the highly swellable polymer of the above type can improve the affinity between the negative electrode sheet and the electrolyte, so that the negative electrode sheet can effectively absorb and retain the electrolyte, reduce the transfer resistance of lithium ions on the interface, and thus improve the electrochemical performance and charge and discharge efficiency of the battery.

[0048] In some embodiments of the present application, the modified polyethylene oxide includes but is not limited to at least one of maleic anhydride-modified polyethylene oxide, acrylic anhydride-modified polyethylene oxide, methacrylic anhydride-modified polyethylene oxide, fumaric acid-modified polyethylene oxide, acrylic acid-modified polyethylene oxide, and methacrylic acid-modified polyethylene oxide. Thus, the affinity of polyethylene oxide can be improved, and the affinity between polyethylene oxide and electrolyte can be improved under the premise of having high swelling performance, so that it can absorb more electrolyte, increase the mobility of lithium ions, and improve the fast charging performance of the battery.

[0049] In some embodiments of the present application, the modified polyethylene oxide is obtained by the following method: esterification reaction is carried out between the modified monomer and polyethylene oxide to obtain the modified polyethylene oxide; wherein the modified monomer includes at least one of maleic anhydride monomer, acrylic anhydride monomer, methacrylic anhydride monomer, fumaric acid monomer, acrylic acid monomer, and methacrylic acid monomer. Thus, the method can improve the affinity of polyethylene oxide (PEO), so that the polyethylene oxide has a high swelling property, improves the affinity between polyethylene oxide and the electrolyte, enables it to absorb more electrolyte, increase the mobility of lithium ions, and improve the fast charging performance of the battery.

[0050] In some embodiments of the present application, the weight ratio of the modified monomer to the polyethylene oxide is (0.2:30)-(1:70). For example, it can be 0.2:30, 0.5:40, 0.7:50, 0.9:60, 1:70, etc., or can be a range composed of any of the above values. Therefore, by making the weight ratio of the modified monomer to the polyethylene oxide within the above range, the affinity of the polyethylene oxide can be better improved, thereby improving the ability of the polyethylene oxide to absorb electrolyte.

[0051] In some embodiments of the present application, the maleic anhydride-modified polyethylene oxide is obtained by the following method: maleic anhydride monomer is subjected to an esterification reaction with polyethylene oxide to obtain the maleic anhydride-modified polyethylene oxide. Thus, the method can improve the affinity of polyethylene oxide (PEO), so that the polyethylene oxide has a high swelling property, and improves the affinity between polyethylene oxide and the electrolyte, so that it can absorb more electrolyte, increase the mobility of lithium ions, and improve the fast charging performance of the battery.

[0052] In some embodiments of the present application, the weight ratio of the maleic anhydride monomer to the polyethylene oxide is (0.2:30)-(1:70). For example, it can be 0.2:30, 0.5:40, 0.7:50, 0.9:60, 1:70, etc., or can be a range composed of any of the above values. Thus, by making the weight ratio of the maleic anhydride monomer to the polyethylene oxide within the above range, the affinity of the polyethylene oxide can be better improved, thereby improving the ability of the polyethylene oxide to absorb electrolyte.

[0053] In some embodiments of the present application, the solvent for the esterification reaction is tetrahydrofuran.

[0054] In some embodiments of the present application, the esterification reaction is carried out under the action of a catalyst, 4-dimethylaminopyridine, thereby improving the affinity of polyethylene oxide and thus improving the ability of polyethylene oxide to absorb electrolyte.

[0055] In some embodiments of the present application, the esterification reaction is carried out at 60° C. to 80° C. for 4 to 8 hours. Thus, the affinity of polyethylene oxide can be improved, thereby improving the ability of polyethylene oxide to absorb electrolyte.

[0056] Illustratively, the esterification reaction can be carried out at 60° C., 65° C., 70° C., 75° C., 80° C., or a range consisting of any of the above values.

[0057] Illustratively, the esterification reaction time is 4 h, 5 h, 6 h, 7 h, 8 h, etc., or a range consisting of any of the above values.

[0058] In some embodiments of the present application, the negative electrode slurry further includes but is not limited to at least one of a thickener and a binder. The thickener can increase the viscosity of the negative electrode slurry so that it can be evenly covered on the current collector; the binder can firmly adhere other substances in the negative electrode slurry to the current collector to ensure that they will not fall off during the battery charging and discharging process.

[0059] In some embodiments of the present application, the thickener includes but is not limited to at least one of sodium carboxymethyl cellulose (CMC-Na) and lithium carboxymethyl cellulose (CMC-Li). Thus, the above-mentioned thickeners can increase the viscosity of the negative electrode slurry without affecting the properties of other substances, so that it can be evenly covered on the current collector during the coating process.

[0060] In some embodiments of the present application, the binder includes but is not limited to at least one of styrene-butadiene rubber (SBR) and polyacrylate (PAA). Thus, the above-mentioned binders can firmly adhere various substances to the current collector without affecting the performance of other substances, ensuring that the battery will not fall off during the charging and discharging process.

[0061] In some embodiments of the present application, the mass ratio of the negative electrode active material, the conductive agent with a porous structure, the highly swellable polymer, the thickener and the binder is (90-98): (0.5-5.0): (0.1-1.0): (0.5-3): (0.8-5.0), based on the total mass of the negative electrode active material, the conductive agent with a porous structure, the highly swellable polymer, the thickener and the binder as 100 parts. For example, it can be 90:4:1:2:3, 92:3:0.5:1.5:3, 95:1:0.3:2.7:1, 98:0.5:0.1:0.5:0.9, 90:1.9:0.1:3:5, 91:5:0.7:2.5:0.8, etc., or a range consisting of any of the above values. Therefore, by precisely adjusting the mass ratio of the negative electrode active material, the conductive agent with a porous structure, the highly swellable polymer, the thickener and the binder, the performance of the negative electrode slurry can be optimized, thereby improving the fast charging performance and cycle stability of the battery. The negative electrode slurry obtained according to the above ratio helps to build a rich lithium ion transmission channel, improve the conductivity of lithium ions, and accelerate the charge and discharge reaction speed of the battery. At the same time, it enhances the affinity between the negative electrode material and the electrolyte, improves the absorption and retention capacity of the electrolyte, and provides sufficient lithium ions for fast charging. In addition, precise control of the proportion of each component can not only improve the performance of the battery, but also effectively control the cost while ensuring the energy density and power density.

[0062] The present application proposes a method for preparing the negative electrode slurry described above. According to an embodiment of the present application, the method includes: subjecting the negative electrode active material, the conductive agent having a porous structure and the highly swellable polymer to a first mixing treatment to obtain the negative electrode slurry. Through the method of the present application, a negative electrode slurry having abundant lithium ion transmission channels, good lithium ion conductivity, and good ability to absorb and retain electrolyte can be obtained. Those skilled in the art can understand that this method has all the characteristics and advantages of the negative electrode slurry described above, and will not be described in detail here.

[0063] In some embodiments of the present application, the method further includes: subjecting the negative electrode active material, the conductive agent having a porous structure, the highly swellable polymer, the thickener and the binder to the first mixing treatment.

[0064] Negative electrode sheet and preparation method thereof

[0065] The present application proposes a negative electrode sheet. According to an embodiment of the present application, the negative electrode sheet is prepared from the negative electrode slurry described above. As mentioned above, the negative electrode slurry of the present application can provide more lithium ion channels, improve ion conductivity, and has good electrolyte absorption and electrolyte retention capabilities. Therefore, the negative electrode sheet prepared using the negative electrode slurry of the present application has good conductivity and can improve the cycle performance and high rate performance of lithium-ion batteries. Those skilled in the art can understand that the negative electrode sheet has all the characteristics and advantages of the negative electrode slurry described above, and will not be repeated here.

[0066] The present application proposes a method for preparing the negative electrode sheet mentioned above. According to an embodiment of the present application, the method includes: providing a negative electrode current collector, coating the negative electrode slurry mentioned above on at least one side of the surface of the negative electrode current collector, and drying to obtain the negative electrode sheet. The negative electrode sheet prepared by the method of the present application can provide more lithium ion channels, has good ion conductivity, and has good absorption and retention ability for electrolyte, thereby improving the cycle performance and fast charging performance of the battery. Those skilled in the art can understand that this method has all the characteristics and advantages of the negative electrode slurry described above, and will not be repeated here.

[0067] Battery

[0068] The present application proposes a battery. According to an embodiment of the present application, the battery includes the negative electrode sheet described above. As a result, the lithium-ion battery of the present invention has better cycle performance, high rate performance, etc. It can be understood by those skilled in the art that the lithium-ion battery has all the features and advantages of the negative electrode slurry described above, and no further elaboration is given here.

[0069] In some embodiments of the present application, the battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0070] In some embodiments of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0071] Exemplarily, when the positive electrode sheet is used in a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O 2 ) or at least one of its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate or a composite material of lithium iron manganese phosphate and carbon.

[0072] In some embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite positive electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0073] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0074] In some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0075] In some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet (such as positive electrode active material, conductive agent, binder) are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0076] In some embodiments of the present application, the electrolyte includes a lithium salt and a solvent.

[0077] Exemplarily, the lithium salt includes lithium hexafluorophosphate (LiPF 6), at least one of lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethanesulfonate, bis(trifluoromethylsulfonyl)methyllithium, and tris(trifluoromethylsulfonyl)methyllithium.

[0078] Exemplarily, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, ethylene carbonate, vinylene carbonate (VC), methyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, ethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, propyl vinylene carbonate, 1,2-dipropyl vinylene carbonate, vinyl ethylene carbonate (VEC), divinyl ethylene carbonate (DVEC), methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate.

[0079] The present invention has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. According to an embodiment of the present application, the isolation membrane may be made of at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.

[0080] In some embodiments of the present application, the battery may include an outer package for packaging a positive electrode sheet, a negative electrode sheet, and an electrolyte.

[0081] In some embodiments of the present application, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.

[0082] In some embodiments of the present application, the outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.

[0083] The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0084] The battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0085] The present application proposes an electric device. According to an embodiment of the present application, the electric device includes the aforementioned battery. Therefore, the electric device of the present application has good cycle performance, fast charging performance, and excellent service life and safety performance.

[0086] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.

[0087] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0088] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0089] As another embodiment, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0090] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0091] Example 1

[0092] 1. Preparation of high swelling rate polymer:

[0093] First, 0.6 parts by weight of maleic anhydride was added to the reactor, and the mixture was dissolved in 300 parts by weight of tetrahydrofuran (THF) by stirring at 200 rpm for 30 min. Then, 50 parts by weight of polyethylene oxide powder was gradually added at the same speed, and a catalytic amount of 4-dimethylaminopyridine (DMAP) was added. The esterification reaction was carried out at 80° C. for 6 h. Finally, the final product, maleic anhydride-modified polyethylene oxide, was obtained by solvent drying, separation and purification.

[0094] 2. Preparation of negative electrode

[0095] The negative electrode active material is artificial graphite, the conductive agent is mesoporous conductive carbon black, the thickener is CMC-Na, the binder is SBR, the additive (highly swellable polymer) is maleic anhydride-modified polyethylene oxide prepared in step 1, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive is 96:1.5:1:1.3:0.2, and the solvent is deionized water.

[0096] The above materials were fully stirred and mixed in deionized water to obtain negative electrode slurry, and the solid content of the slurry was controlled to be 45±15% and the viscosity (64# rotor) was controlled to be within the range of 4000±2000 cP.

[0097] After filtering the negative electrode slurry through a 100-300 mesh screen, inject it into the die cavity structure and evenly coat it on both sides of the copper foil, and adjust the surface density to meet the preset value range. After drying, the semi-finished negative electrode sheet is obtained. The coated electrode sheet is rolled to a certain thickness by a cold roller or an oil-heated roller to reach the preset compaction density range. The rolled negative electrode sheet is adjusted to the specified size by a slitting tool or laser cutting to obtain a negative electrode sheet.

[0098] 3. Preparation of positive electrode

[0099] The positive electrode sheet is made of LiFePO 4 (LFP): polyvinylidene fluoride (PVDF): conductive paste = 97:2:1, obtained after mixing, coating, rolling and slitting.

[0100] The conductive paste is prepared from carbon nanotubes and N-methylpyrrolidone (NMP) solvent, and the mass ratio of the carbon nanotubes to the N-methylpyrrolidone (NMP) solvent is 15:85.

[0101] 4. Preparation of test cells

[0102] The negative electrode sheet, positive electrode sheet, separator (polypropylene PP), electrolyte (LiPF 6 +EC / DMC) and aluminum-plastic film to assemble into test cells.

[0103] Example 2

[0104] The negative electrode sheet, the positive electrode sheet and the test battery cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass proportion of the mesoporous conductive carbon black was 0.5%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 97:0.5:1:1.3:0.2.

[0105] Example 3

[0106] The negative electrode sheet, the positive electrode sheet and the test battery cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass proportion of the mesoporous conductive carbon black was 3%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 94.5:3:1:1.3:0.2.

[0107] Example 4

[0108] The negative electrode sheet, the positive electrode sheet and the test battery cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass proportion of the mesoporous conductive carbon black was 5%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 92.5:5:1:1.3:0.2.

[0109] Example 5

[0110] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass proportion of maleic anhydride-modified polyethylene oxide was 0.1%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 96.1:1.5:1:1.3:0.1.

[0111] Example 6

[0112] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass proportion of maleic anhydride-modified polyethylene oxide was 0.5%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 95.7:1.5:1:1.3:0.5.

[0113] Example 7

[0114] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass ratio of maleic anhydride-modified polyethylene oxide was 1%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 95.2:1.5:1:1.3:1.

[0115] Example 8

[0116] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass ratio of maleic anhydride-modified polyethylene oxide was 1%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 94.2:1.5:1:1.3:2.

[0117] Example 9

[0118] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, microporous conductive graphite replaced the mesoporous conductive carbon black.

[0119] Example 10

[0120] The negative electrode sheet, the positive electrode sheet and the test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mesoporous conductive carbon black was replaced by the microporous conductive activated carbon.

[0121] Embodiment 11

[0122] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, mesoporous conductive graphene replaced the mesoporous conductive carbon black.

[0123] Example 12

[0124] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, polyacrylate replaced the maleic anhydride-modified polyethylene oxide.

[0125] Embodiment 13

[0126] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, polyacrylamide replaced the maleic anhydride-modified polyethylene oxide.

[0127] Embodiment 14

[0128] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass fraction of CMC-Na was 0.5%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 96.5:1.5:0.5:1.3:0.2.

[0129] Embodiment 15

[0130] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass fraction of CMC-Na was 3%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 94.5:1.5:3:1.3:0.2.

[0131] Example 16

[0132] The negative electrode sheet, the positive electrode sheet and the test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass fraction of SBR was 0.8%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 96.5:1.5:1:0.8:0.2.

[0133] Embodiment 17

[0134] The negative electrode sheet, the positive electrode sheet and the test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the mass fraction of SBR was 5%, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener, the binder and the additive was 92.3:1.5:1:5:0.2.

[0135] Comparative Example 1

[0136] The negative electrode sheet, the positive electrode sheet and the test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, the negative electrode conductive agent did not use a conductive agent with a porous structure, but used ordinary conductive carbon black SP.

[0137] Comparative Example 2

[0138] The negative electrode sheet, the positive electrode sheet and the test cell were prepared according to the method described in Example 1, except that when preparing the negative electrode sheet, no additive (highly swellable polymer) was added to the negative electrode slurry, that is, the mass ratio of the negative electrode active material, the conductive agent, the thickener and the binder was 96.2:1.5:1:1.3.

[0139] The differences between Examples 1-17 and Comparative Examples 1 and 2 are shown in Table 1.

[0140] Table 1

[0141]

[0142]

[0143]

[0144] Embodiment 18

[0145] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that 1.0 parts by weight of maleic anhydride and 70 parts by weight of polyethylene oxide powder were used in the preparation of the high swelling rate polymer.

[0146] Embodiment 19

[0147] A negative electrode sheet, a positive electrode sheet and a test cell were prepared according to the method described in Example 1, except that 0.2 parts by weight of maleic anhydride and 30 parts by weight of polyethylene oxide powder were used in the preparation of the high swelling rate polymer.

[0148] The differences between Example 1 and Examples 18-19 are shown in Table 2.

[0149] Table 2

[0150]

[0151]

[0152] Performance Test:

[0153] 1. Liquid absorption test: Cut the negative electrode sheets of Examples 1-19 and Comparative Examples 1-2 to a size of 70mm×65mm; fill the electrolyte container with electrolyte to the specified scale; install the negative electrode sheets on the hooks respectively, start the lifting platform, raise the electrolyte container to the required height, ensure that the negative electrode sheets are completely immersed in the electrolyte, and the immersion time is 30min; start the lifting platform, lower the electrolyte container to the lowest level, and keep the hanging state for 1h; use the test equipment to record the weight change curve throughout the process. The starting weight of the negative electrode sheet is M1, the weight change during the immersion process, the weight of the negative electrode sheet when the immersion is stable, the weight of the negative electrode sheet when it is pulled out of the liquid surface, the weight change during the static process, and the final weight of the negative electrode sheet at the static end is M2. Among them, the weight change of the negative electrode sheet during the immersion and static stages is at the mg level, which has no obvious effect on the test results and can be assumed to be no change. The liquid retention rate calculation formula is: liquid retention rate = (M2-M1) / M1.

[0154] 2. High rate charge and discharge DCR test: The test cells of Examples 1-19 and Comparative Examples 1-2 were charged to Vmax at 25°C ± 3°C with a charging current density of 0.33C and a cut-off current of 0.05C, and then allowed to stand for 0.5h. They were then discharged at a discharge current density of 0.33C for 90min, and the static voltage V0 was recorded after standing for 0.5h. They were discharged at a discharge current density of 4C for 10s, and the static voltage V1 was recorded. After standing for 1min, they were charged at a charging current density of 0.33C for 120s, and the static voltage V2 was recorded after standing for 0.5h. They were charged at a charging current density of 4C for 10s, and the static voltage V3 was recorded. The instantaneous charge DCR and discharge DCR were calculated.

[0155] 3. Fast charge cycle test: Place the test cells of Examples 1-19 and Comparative Examples 1-2 in an environment of 25°C±3°C, with a charge and discharge voltage of 2.8~4.5V (NCM), 2.5~4.2V (LFP), a charging current density of 3C, a discharging current density of 1C, and a cut-off current of 0.05C. Cycle 800 times according to the above process, and calculate the fast charge cycle capacity retention rate based on the discharge capacity at the 800th cycle / the discharge capacity at the 1st cycle.

[0156] The test results are shown in Table 3. It can be seen that after using ordinary conductive carbon black SP and not adding high swelling polymer in Comparative Examples 1 and 2, the liquid absorption and liquid retention capacity of the negative electrode sheet is significantly worse than that in Example 1, and the charge and discharge DCR and fast charge cycle capacity retention rate are also worsened;

[0157] In Examples 1, 3 and 4, the liquid absorption and liquid retention capabilities are better than those in Example 2 due to the gradual increase in the amount of mesoporous conductive carbon black added, and the increase in ion transmission channels significantly reduces the charge and discharge DCR and improves the fast charge cycle capacity retention rate;

[0158] In Example 5, since the amount of maleic anhydride-modified polyethylene oxide added was halved, the liquid absorption and liquid retention capabilities were lower than those in Example 1;

[0159] In Examples 6-8, as the amount of maleic anhydride-modified polyethylene oxide added gradually increased, the liquid absorption and liquid retention capabilities gradually increased compared with Example 1. However, since maleic anhydride-modified polyethylene oxide is not conductive, excessive addition leads to a significant increase in charge and discharge DCR, thereby affecting the fast charge cycle capacity retention rate;

[0160] In Examples 9-11, the mesoporous conductive carbon black is replaced with microporous conductive graphite, microporous conductive activated carbon, and mesoporous conductive graphene in sequence, and the performance is not much different from that of Example 1;

[0161] In Examples 12-13, the maleic anhydride-modified polyethylene oxide is replaced by polyacrylate and polyacrylamide in sequence. Although the liquid absorption and liquid retention capabilities are comparable to those in Example 1, the charge-discharge DCR and the fast-charge cycle capacity retention rate deteriorate.

[0162] In Examples 14-17, the addition ratio of CMC and SBR was adjusted, and the performance was not much different from that of Example 1;

[0163] The modification ratio of maleic anhydride to polyethylene oxide in Examples 18-19 is adjusted, which is not much different from that in Example 1.

[0164] Table 3

[0165] Liquid absorption height / mm Fluid retention rate / % Charging DCR / mΩ Discharge DCR / mΩ Fast charge capacity retention rate Example 1 2.3 30.9 17.6 18.7 90.3% Example 2 1.7 28.2 23.7 24.1 88.7% Example 3 3.2 32.1 13.5 14.2 91.2% Example 4 3.9 34.6 11.3 11.9 92.1% Example 5 2.2 28.5 17.1 18.2 90.1% Example 6 2.3 33.0 18.7 19.1 89.9% Example 7 2.3 35.3 24.5 26.1 88.6% Example 8 2.4 37.2 29.7 30.5 88.1% Example 9 2.4 31.1 17.3 18.2 90.5% Example 10 2.3 30.9 17.5 18.6 90.4% Embodiment 11 2.2 30.7 18.0 19.1 90.1% Example 12 2.1 31.0 20.3 21.3 88.2% Embodiment 13 2.0 30.8 21.0 21.8 88.4% Embodiment 14 2.1 29.8 17.0 17.9 90.1% Embodiment 15 2.3 30.8 20.3 21.0 89.2% Example 16 2.2 28.7 17.1 17.7 90.0% Embodiment 17 2.4 32.1 22.5 23.9 89.7% Embodiment 18 2.2 30.8 18.1 19.0 89.7% Embodiment 19 2.5 31.3 18.0 19.1 90.2% Comparative Example 1 1.3 25.2 22.7 23.1 86.7% Comparative Example 2 1.3 24.9 21.9 22.6 87.1%

[0166] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A negative electrode slurry, characterized in that: include: A negative electrode active material, a conductive agent with a porous structure and a highly swellable polymer.

2. The negative electrode slurry according to claim 1, characterized in that: Based on the total mass of the negative electrode slurry, the mass proportion of the conductive agent with a porous structure is 0.5%-5%; And / or, based on the total mass of the negative electrode slurry, the mass proportion of the highly swellable polymer is 0.1%-1%.

3. The negative electrode slurry according to claim 1, characterized in that: The conductive agent includes at least one of carbon black, graphite, and activated carbon; And / or, the negative electrode active material includes at least one of a carbon material or an alloy material; And / or, the highly swellable polymer includes at least one of polyacrylate, polyacrylamide, and modified polyethylene oxide.

4. The negative electrode slurry according to claim 3, characterized in that: The pore size of the porous structure is no greater than 50 nm; And / or, the specific surface area of ​​the conductive agent is 200m 2 / g-2000m 2 / g; And / or, the carbon material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, petroleum coke, carbon fiber, pyrolytic carbon, and resin carbon; And / or, the alloy material includes at least one of tin-based alloy, silicon-based alloy, germanium-based alloy, aluminum-based alloy, antimony-based alloy, and magnesium-based alloy; And / or, the modified polyethylene oxide includes at least one of maleic anhydride-modified polyethylene oxide, acrylic anhydride-modified polyethylene oxide, methacrylic anhydride-modified polyethylene oxide, fumaric acid-modified polyethylene oxide, acrylic acid-modified polyethylene oxide, and methacrylic acid-modified polyethylene oxide.

5. The negative electrode slurry according to claim 3, characterized in that: The modified polyethylene oxide is obtained by the following method: Carrying out an esterification reaction between the modified monomer and polyethylene oxide to obtain the modified polyethylene oxide; Wherein, the modified monomer includes at least one of maleic anhydride monomer, acrylic anhydride monomer, methacrylic anhydride monomer, fumaric acid monomer, acrylic acid monomer, and methacrylic acid monomer.

6. The negative electrode slurry according to claim 5, characterized in that: The weight ratio of the modified monomer to the polyethylene oxide is (0.2:30)-(1:70); And / or, the solvent for the esterification reaction is tetrahydrofuran; And / or, the esterification reaction is carried out under the action of a catalyst 4-dimethylaminopyridine; And / or, the esterification reaction is carried out at 60° C. to 80° C. for 4 h to 8 h.

7. The negative electrode slurry according to claim 1, characterized in that: Further comprising at least one of a thickener and a binder.

8. The negative electrode slurry according to claim 7, characterized in that: The mass ratio of the negative electrode active material, the conductive agent having a porous structure, the highly swellable polymer, the thickener and the binder is (90-98):(0.5-5.0):(0.1-1.0):(0.5-3):(0.8-5.0).

9. A negative electrode sheet, characterized in that: The negative electrode slurry is prepared from the negative electrode slurry described in any one of claims 1 to 8.

10. A battery, characterized in that: Including the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of thick electrode with excellent electrochemical performance and lithium ion battery

    CN107093701A

  • Thick negative pole piece, preparation method thereof and lithium ion battery

    CN113571673A

  • Lithium ion battery negative plate as well as preparation method and application thereof

    CN115207357A

  • Diaphragm and electrochemical device and electronic device comprising diaphragm

    CN116169428A

  • Positive plate, lithium ion battery with positive plate and electronic equipment

    CN116435512A

Cited By

  • Negative electrode slurry, negative electrode sheet, and battery

    WO2026145724A1